Tooth avulsion – report of two cases - Ciesielski, Piotr; Sulwińska, Mia; Łaszkiewicz, Joanna (Journal of Stomatology, 2015)
Introduction. Tooth avulsion, also referred to as total luxation, is described as complete displacement of the tooth from the alveolus. In avulsion, replantation of the tooth is the treatment of choice. It is followed by temporary splinting of teeth and, when necessary, endodontic treatment and antibiotic therapy. Aim of the study. To present two cases of total luxation of teeth followed by their replantation. Material and methods. Replantation was conducted in two patients aged 10 and 9 years. The extra-alveolar time for the teeth was 30 min and 3.5 hours, respectively. Both teeth were stored in dry conditions. In the first case, endodontic treatment was initiated by the referring dentist two months after the trauma occurring upon diagnosis of inflammatory resorption. In the second case, endodontic treatment was started after 48 hours. In both cases, root canals were filled with ProRoot MTA. Results. In the first case, 5-year-long observation period revealed arrested inflammatory resorption primarily caused by initial delay in the root canal therapy of the avulsed tooth. In the latter case, in which endodontic treatment was undertaken after an appropriate lapse of time, too long extra-alveolar time resulted in ankylosis. Conclusion. Long-term positive therapeutic outcome in dental avulsion depends on the extra-alveolar time and storage conditions of the tooth prior to replantation. The time at which endodontic treatment is initiated also plays a pivotal role, as demonstrated in the article.